1986
DOI: 10.1007/bf00213929
|View full text |Cite
|
Sign up to set email alerts
|

Acid phosphatase activity and intracellular collagen degradation by fibroblasts in vitro

Abstract: Human gingival fibroblasts were cultured with collagen fibrils. The precise process of collagen phagocytosis and the relationship between acid phosphatase activity and intracellular degradation of collagen were investigated by cytochemical methods at the ultrastructural level. The collagen fibrils were first engulfed at one end by cellular processes, or the cell membrane wrapped itself around the middle of the fibrils. Collagen phagocytosis induced acid phosphatase activity in the fibroblast Golgi-endoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Secondary lysosomes and macroautophagosomes contain acid phosphatase, a lysosomal enzyme that in part functions to degrade contents such as collagen within these structures (Dunn, 1990b; Yajima, 1986). Acid phosphatase activity was assessed in HPS‐1 melanocytes at the electron microscopic level using the technique developed by Gomori (1952).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary lysosomes and macroautophagosomes contain acid phosphatase, a lysosomal enzyme that in part functions to degrade contents such as collagen within these structures (Dunn, 1990b; Yajima, 1986). Acid phosphatase activity was assessed in HPS‐1 melanocytes at the electron microscopic level using the technique developed by Gomori (1952).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated acid phosphatase activity in the electron-dense type of vacuoles, indicating the presence of lysosomal enzymes ( Fig. 2; Deporter & Ten Cate, 1973;Beertsen et aI., 1978;Everts et al, 1985b;Yajima, 1986Yajima, , 1988. Some authors localized the enzyme also in electron-translucent vacuoles (Beertsen et al, 1978).…”
Section: Fibroblastsmentioning
confidence: 90%
“…We hypothesize that the fibroblasts interact with HDSC by production and release of, e.g., proteolytic enzymes (such as collagenase) [28][29][30][31] into the culture gel, reaching HDSC by diffusion, resulting in its degradation. The molecular structure of (cytotoxic) degradation products may depend on the available binding sites on the collagen for proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%